2021
DOI: 10.7759/cureus.13414
|View full text |Cite
|
Sign up to set email alerts
|

Race, Income, and the Timeliness of Cleft Palate Repair in the United States

Abstract: Objective To determine if differences exist in the timing of cleft palate repair with respect to sex, race, income, and geographical location within the United States. Design Retrospective cross-sectional study using the Kids’ Inpatient Database (KID) from 1997 to 2009. Setting Inpatient. Patients Children with cleft palate with or without cleft lip undergoing inpatient cleft palate repair. Main outcome measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…We have shown that children with congenital anomalies in general and those with specific anomalies have far longer hospital stays than children without congenital anomalies and this cannot only be explained by the surgeries needed for their congenital anomaly. For most of the specific congenital anomalies included in this study surgery takes place within the first year after birth, although for children with a cleft palate or hypospadias corrective surgery may take place later [23][24][25][26]. Despite that, children with congenital anomalies are also more often hospitalised at ages 1-4 years and median LOS is longer compared to reference children.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that children with congenital anomalies in general and those with specific anomalies have far longer hospital stays than children without congenital anomalies and this cannot only be explained by the surgeries needed for their congenital anomaly. For most of the specific congenital anomalies included in this study surgery takes place within the first year after birth, although for children with a cleft palate or hypospadias corrective surgery may take place later [23][24][25][26]. Despite that, children with congenital anomalies are also more often hospitalised at ages 1-4 years and median LOS is longer compared to reference children.…”
Section: Discussionmentioning
confidence: 99%
“…We do not know why these differences occurred. Early surgery for a cleft palate may have a negative impact on the growth of the maxilla and late surgery may have a negative impact on speech development 18,19 . The recommended age for surgery for hypospadias is 6–18 months or later in childhood 19‐21 .…”
Section: Discussionmentioning
confidence: 99%
“…Early surgery for a cleft palate may have a negative impact on the growth of the maxilla and late surgery may have a negative impact on speech development. 18,19 The recommended age for surgery for hypospadias is 6-18 months or later in childhood. [19][20][21] Small anatomy may be a surgical challenge, but one study reported that adolescents who are not able to recall the surgery seemed to have a more positive body image.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases of postpartum death were associated with severe syndromes, which were not explored in depth in this study, which is a weakness of this study. After prenatal diagnosis, the severity of CL/P and family economic conditions are also important factors affecting abortion (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%